Edukasi Teknologi Bioflok Ikan Lele Sebagai Upaya Meningkatkan Gizi Siswa Pondok Pesantren Darul Khuldi - Eka Rizki Meiwinda; Siska Almaniar; Rahmawaty Hasibuan; Arabiatul Adawiyah; R Zicky Chandra Kesuma (Universitas Dehasen Bengkulu, 2024)
Islamic boarding schools currently have many activities, apart from teaching and learning activities but also utilize other activities such as in the agricultural, plantation and fisheries sectors in order to utilize school land and as an effort to meet students' food needs. Catfish Biofloc Technology Education is one method used to teach students about how to cultivate fish in biofloc ponds. With this cultivation, it is hoped that it will become an additional source of income for the school. This service was carried out at the Darul Khuldi Islamic Boarding School, Ogan Komering Ulu Regency. Community service method carried out through education regarding raising catfish in biofloc ponds. Ultimately, with this activity, it is hoped that it will function as a food security program and increase sources of income for Islamic boarding schools.